Fear and anxiety in Dental Practice: A Review - Sadat, SM Anwar; Nishi, Nowrin Jahan; Palash, Md Jahidul Islam; Rita, Sufia Nasrin (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Fear is expressed as an unpleasant emotion caused by threat of danger, pain and harm. Anxiety is an emotional state of a person such as doubt, mental-conflict, and disappointment. Phobia is persistent, unrealistic and intense fear of a specific stimulus, leading to absolute avoidance of the perceived danger. Corah’s Dental Anxiety Scale (CDAS), Modified Dental Anxiety Scale (MDAS), and Dental Fear Survey (DFS) are the tools to assess fear and anxiety. Dental fear and anxiety can be managed by change in dental set up and office environment, improving communication skill of practitioner and trust building among patients. Other approaches like behaviour-management techniques e.g., technique of relaxation, attention distraction, hypnotherapy, positive reinforcement, systematic desensitization and pharmacological management e.g., general anaesthesia and conscious sedation are also used to prevent and treat dental fear and anxiety in dental practice. J Bangladesh Coll Phys Surg 2022; 40: 292-298